Evaluation of professional satisfaction of audiologists working in Türkiye based on their personality characteristics and sector of work - Çelikgün, Bahtiyar; Büyükkal, Furkan; Minga, Recep; Ölçek, Gül (Frontiers in Psychology, 2024)
Purpose: This study investigates the relationship between audiologists' personality traits and professional satisfaction.Design: Big Five-50 Personality Traits and Professional Satisfaction Scale was used to examine the relationship between audiologists' personality traits and professional satisfaction. Statistical analyzes were performed with SPSS and AMOS programs.Study Example: This study examines 167 audiologists who completed a minimum of an undergraduate program in audiology before the professional field.The results of confirmatory factor analysis indicate that both scales are reliable and valid. There is a significant relationship between extraversion, agreeableness, conscientiousness, and emotional stability and occupational satisfaction. However, there is no significant relationship between intelligence/imagination and professional satisfaction.Extraversion, agreeableness, conscientiousness, emotional stability/neuroticism affect job satisfaction. Understanding these dynamics can inform strategies that will increase the professional well-being and productivity of audiologists.